Can You Hear Me Now? Augmentative Communication, Methodological Empowerment, and the Life Story of Jon Feucht - Flad, Jennifer; Berger, Ronald J.; Feucht, Jon (Disability Studies Quarterly, 2011)
Keywords augmentative communication, disability, biography, methodology Abstract Feminist social research and disability studies converge in arguing for a research methodology undertaken on behalf of and to empower research participants. Our research, an ongoing life history project with Jon Feucht, has been undertaken in this tradition. Throughout much of his life, Jon struggled with a severe speech disability due to cerebral palsy that significantly impaired his ability to communicate verbally with others. After acquiring a sophisticated augmentative communication device, Jon's life changed for the better. In this paper we describe the nature of augmentative communication, share some of Jon's thoughts about augmentative communication and people with disabilities, and explore some of the challenges and opportunities facing researchers collaborating on research projects with individuals who use augmentative communication to speak.